Nucleus basalis of Meynert revisited: anatomy, history and differential involvement in Alzheimer’s and Parkinson’s disease - Liu, Alan King Lun (Acta Neuropathol, 2015)
It has been well established that neuronal loss within the cholinergic nucleus basalis of Meynert (nbM) correlates with cognitive decline in dementing disorders such as Alzheimer’s disease (AD). Friedrich Lewy first observed his eponymous inclusion bodies in the nbM of postmortem brain tissue from patients with Parkinson’s disease (PD) and cell loss in this area can be at least as extensive as that seen in AD. There has been confusion with regard to the terminology and exact localisation of the nbM within the human basal forebrain for decades due to the diffuse and broad structure of this “nucleus”. Also, while topographical projections from the nbM have been mapped out in subhuman primates, no direct clinicopathological correlations between subregional nbM and cortical pathology and specific cognitive profile decline have been performed in human tissue. Here, we review the evolution of the term nbM and the importance of standardised nbM sampling for neuropathological studies. Extensive review of the literature suggests that there is a caudorostral pattern of neuronal loss within the nbM in AD brains. However, the findings in PD are less clear due to the limited number of studies performed. Given the differing neuropsychiatric and cognitive deficits in Lewy body-associated dementias (PD dementia and dementia with Lewy bodies) as compared to AD, we hypothesise that a different pattern of neuronal loss will be found in the nbM of Lewy body disease brains. Understanding the functional significance of the subregions of the nbM could prove important in elucidating the pathogenesis of dementia in PD.